Potential of coconut oil as a mosquito repellent - Shiho Hara; Micheal Teron Pillay; Toshihiko Sunahara; Masaru Nagashima; Lucy Atieno Okech; Chiaki Tsurukawa; Yasuhiko Kamiya (Tropical Medicine and Health)
Abstract Background Naturally derived products have become popular as a mosquito repellent in addition to mosquito nets and chemical repellents. Coconut-derived fatty acids have demonstrated repellent properties against various blood-feeding arthropods, including mosquitoes. Daily use moisturizers and body soaps containing coconut have displayed some repellent effect against mosquitoes. However, no studies have been conducted on coconut oil specifically, and the effects of pure coconut oil still remain unknown in the western Kenya region. Methods In this study, we investigated the effect of coconut oil on decreasing mosquito bites in a laboratory and field setting. Using Anopheles stephensi mosquitoes, the laboratory experiment compared coconut oil treated and non-treated membranes on a Hemotek blood feeding device. In the cross-sectional study in western Kenya, we investigated bite counts among 490 children, 5 years and under. Descriptive analysis, simple, multiple and mixed regression models were employed. The outcome was the number of mosquito bite marks, the primary explanatory variable was skin cream types, in addition to demographic, environmental, behavioral and socio-economic variables. Results Coconut oil significantly reduced mosquito blood feeding, with a pooled Mantel–Haenszel odds ratio of 0.06, a Mantel–Haenszel chi-square statistic of 79.82 (p = 0.01), and an average blood-feeding rate of 1% compared to 31% in the control group. The mixed model identified significant factors influencing mosquito bite counts while accounting for village-level random effects. Coconut oil users experienced 15% reduction in bites (p = 0.01) compared to synthetic creams users. High and medium cream application frequencies reduced bites by 57% (p < 0.001) and 17% (p = 0.007), respectively. Late cream application and late net entry significantly increased bite counts by 41% (p < 0.001) and 53% (p < 0.001), respectively. In addition, higher temperatures from the preceding 2 weeks in the region was associated with a 26% (p = 0.003) increase in bite counts. Conclusions These findings underscore the protective impact of cream application and timing and net use timing, as well as environmental temperature influences on bite outcomes. Particularly, the effect of coconut oil in decreasing mosquito bites and its potential as an alternative repellent has been observed in both laboratory and field settings.